Paracetamol versus other analgesia in adult patients with minor musculoskeletal injuries: a systematic review. Issue 8 (22nd June 2019) - Ridderikhof, Milan L; Saanen, Joppe; Goddijn, Helma; Van Dieren, Susan; Van Etten-Jamaludin, Faridi; Lirk, Philipp; Goslings, J Carel; Hollmann, Markus W
Abstract : Objectives: Pain treatment in acute musculoskeletal injuries usually consists of paracetamol, non-steroidal antiinflammatory drugs (NSAIDs) or opioids. It would be beneficial to determine whether paracetamol is as effective as other analgesics. The objective of this study was to evaluate available evidence regarding efficacy of paracetamol in these patients. Methods: Embase, MEDLINE, Cochrane and relevant trial registers were searched from inception to 14 February 2018 by two independent reviewers to detect all randomised studies with adult patients with acute minor musculoskeletal injuries treated with paracetamol as compared with other analgesics. There were no language or date restrictions. Two independent reviewers evaluated risk of bias and quality of evidence. Primary outcome was decrease in pain scores during the first 24 hours, and secondary outcomes included pain decrease beyond 24 hours, need for additional analgesia and occurrence of adverse events. Results: Seven trials were included, evaluating 2100 patients who were treated with paracetamol or NSAIDs or the combination of both as comparisons, of which only four studies addressed the primary outcome. No studies were found comparing paracetamol with opioids. There were no differences in analgesic effectiveness within and beyond 24 hours, nor in need for additional analgesia and occurrence of adverse events. Overall, quality of evidence was low. Because of methodological inconsistencies, a meta-analysis was not possible. Conclusions: Based on available evidence, paracetamol is as effective as NSAIDs or the combination of both in treating pain in adult patients with minor musculoskeletal injuries in the acute setting. The quality of evidence is low.